PENGARUH LOKASI DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN ALFAMART DI KELURAHAN LINGKAR SELATAN KOTA JAMBI - Yenny Yuniarti; Heniyanti Heniyanti (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Modern retail business competition that increasingly characterized by a growing number of retail businesses that stand in various places. Retail business growth not only happens in big cities such as Jakarta, Bandung and Surabaya, but the retail business also developed the message in the town of Jambi. The purpose of this research is to know the influence of the location and the service of the consumer's purchasing decision in simultaneously Alfamart or partially and the dominant factor influencing purchasing decisions. Quantitative descriptive analysis method with the total sample as many as 100 respondents and analysis tool using multiple linear regression analysis. And obtained results that the location and the service affects the purchasing decisions of either simultaneously or partial, where the dominant factor affecting is a service that is of 30.76%.Keywords: location, service, alfamart.